Healthcare applications of federated identity management. (3rd March 2005) - Mead, Brian; Wright, David J.
This paper describes the recent Liberty Alliance standard for Federated Identity Management (FIM) and compares it with other approaches to identity management, with reference to applications in B2E, B2B, and B2B2C e-commerce. It describes international case examples of FIM implementation and identifies ways in which Federated Identity Management can benefit the healthcare industry including doctors in medical buildings, hospital personnel, telemedicine and physicians prescribing medication. It also describes how Federated Identity Management can assist healthcare organisations in complying with privacy legislation.